Cross-Sectional and Time-Series Tests of Return Predictability: What Is the Difference? - Goyal, Amit; Jegadeesh, Narasimhan (Review of Financial Studies, 2018)
We compare the performance of time-series (TS) and cross-sectional (CS) strategies based on past returns. While CS strategies are zero-net investment long/short strategies, TS strategies take on a time-varying net long investment in risky assets. For individual stocks, the difference between the performances of TS and CS strategies is largely due to this time-varying net long investment. With multiple international asset classes with heterogeneous return distributions, scaled CS strategies significantly outperform similarly scaled TS strategies. Received December 7, 2016; editorial decision October 5, 2017 by Editor Andrew Karolyi. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.